Hypericum triquetrifolium and H. neurocalycinum as Sources of Antioxidants and Multi-Target Bioactive Compounds: A Comprehensive Characterization Combining In Vitro Bioassays and Integrated NMR and LC-MS Characterization by Using a Multivariate Approach - Dall’Acqua, Stefano; Ak, Gunes; Sinan, Kouadio Ibrahime; Elbasan, Fevzi; Ferrarese, Irene; Sut, Stefania; Yıldıztugay, Evren; Peron, Gregorio; Schievano, Elisabetta; Nancy Picot-Allain, Marie Carene; Mahomoodally, Mohamad Fawzi; Zengin, Gokhan (Frontiers in Pharmacology, 2021)
The endemic species of Turkey Hypericum triquetrifolium and H. neurocalycinum were evaluated for their phytochemical content and in vitro bioactivity. NMR analyses were performed on the methanol extract of the aerial part of H. triquetrifolium to establish the main classes of phytoconstituents. Then, LC-DAD-MSn analyses were performed in order to compare the composition of aerial parts and roots extracts of both Hypericum spe-cies, obtained using either methanol or water as solvents. Results, processed using multivariate data analysis, showed a significantly higher phenolic content of methanol extracts compared to water extracts, while minor qualitative differences were observed between the two. Distinctive flavonoid and PAC patterns were observed for H. triquetrifolium and H. neurocalycinum, and specific compounds were exclusively detected in one or the other species. Specifically, the phloroglucinols 7-epiclusianone, hyperfirin and hyperforin were present only in H. neurocalycinum, while hyperforin was detected only in H. triquetrifolium. Extracts were assayed using dif-ferent in vitro tests to evaluate their antioxidant properties and their inhibitory activity against several enzymes, showing significant antioxidant and metal chelating activities. Furthermore, inhibitory activities against acetyl-cholinesterase, butyrylcholinesterase and tyrosinase were observed. Multivariate approaches were used to correlate the biological results with the phytochemical composition of the different extracts. Results allowed to determine significant positive correlations between specific compounds and each measured bioactivity, af-fording preliminary data for the further isolation of bioactives from H. neurocalycinum and H. triquetrifolium for pharmacological evaluations.